2020
DOI: 10.1111/apa.15264
|View full text |Cite
|
Sign up to set email alerts
|

Parents' perspectives on dried blood spot self‐sampling from children with epilepsy: A mixed‐method study

Abstract: Self-collection of blood samples in the patient's home environment is an alternative to visits at hospitals for having blood drawn for laboratory blood screening tests. Patients in remote and resource-limited areas and patients with difficulties to access the hospital can have their blood tests collected and sent by mail to the analysing laboratories. 1,2 Dried blood spot sampling is an alternative sampling strategy that has been introduced recently for therapeutic drug monitoring (measuring drug concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Oral sample collection for microbial analysis is a common procedure, but its application is not commonly used in a self-collection setting at home. A recent study on home collection of blood drops by parents of their children suffering from epilepsy concluded that selfsampling at home can reduce stress and decrease the burden of sample collection [24].…”
Section: Discussionmentioning
confidence: 99%
“…Oral sample collection for microbial analysis is a common procedure, but its application is not commonly used in a self-collection setting at home. A recent study on home collection of blood drops by parents of their children suffering from epilepsy concluded that selfsampling at home can reduce stress and decrease the burden of sample collection [24].…”
Section: Discussionmentioning
confidence: 99%